Natural product-inspired strategies towards the discovery of novel bioactive molecules - Sunita Gagare; Pranita Patil; Ashish Jain (SpringerOpen, 2024)
Abstract Background The intricate molecular frameworks of natural products with biological activity towards human targets offer academic and industrial chemists an important starting point for next generation drug discovery. With a focus on natural products for the production of diverse small-molecule libraries and the evaluation of uncharted chemical space, several strategies have emerged for achieving selective modulation of disease-associated targets. This review highlights some of the significant and more recent synthetic strategies inspired by naturally occurring molecular frameworks, aiming at the discovery and development of novel bioactive molecules. We underscore the potential of these innovative strategies with representative examples to forecast their role in addressing the enduring drug design challenge. Main text In this review, we discuss these newer natural product-inspired synthetic approaches, among them diversity-oriented synthesis, biology-oriented synthesis, hybrid natural products, diverted total synthesis, pruning natural products, ring distortion of natural products and integrating natural product framework with a bioactive molecule. Selected representative examples associated with these strategies are given to demonstrate how they have been applied to afford desired bioactivity. Conclusion This review elaborates several pioneering and emerging strategies inspired from natural product which allows access to the unexplored chemical space to identify novel molecules possessing noteworthy bioactivity. The corresponding examples highlight the success of these strategies in the discovery of novel bioactive molecules which can be further developed in drug discovery and can be novel probes for chemical biology. Although there are limited number of successful examples, the selectivity, activity, and efficacy associated with natural product-inspired molecules accentuate their importance.